Analysis of the Paris 2024 Olympic Games in combat sports - Abduqunduzov, A. (Mental Enlightenment Scientific-Methodological Journal, 2025)
This article presents an analysis of the results of the Paris 2024 Olympic Games in combat sports, the most prestigious competition of the four-year cycle. It discusses the successes of new champions and the failures of reigning champions in freestyle, Greco-Roman, and women's wrestling across various weight categories. The main goal is to ensure thorough preparation for future competitions and to study the training and preparation processes of the victorious athletes in order to provide worthy competition at upcoming Olympic Games.